Impact of Remelting on ZnAl4Cu3 Alloy with Addition of Cd on Selected Technological and Mechanical Properties - Dana Bolibruchová; Marek Bruna; Marek Matejka (Metals, 2022)
One of the main objectives in order to increase economic efficiency in foundries is to determine the ratio of the scrap material which can be used in the further manufacture. This factor is important for determining the final prices of products and their competitiveness, given that the prices of zinc on world markets have increased significantly in the recent years. This article deals with the possibilities of remelting the zinc foundry alloy ZnAl4Cu3 and also evaluates the effect of cadmium on selected properties. The main goal is to provide a comprehensive view of the influence of these two factors on selected mechanical properties, casting properties, and microstructure. An important part of the research is to point out the combined influence of given factors. The results of experiments confirmed that an addition of 3 wt.% of Cd has a significant impact on technological and mechanical properties. Fluidity values compared to the Cd-free alloy increased by 22.4%. In terms of mechanical properties, the influence of Cd on the tensile strength was most visible, with a decrease in average by 25 MPa.